Tracing embodied knowledge in the history of science and medicine: expanding the role of film in historical research - Paul Craddock; Anna Harris (Science Museum Group Journal)
Tracing bodily knowledge in medical histories is a challenging task for researchers. Sensory, material and affective details are hard to find in archival sources and hard to put into words. Researchers have found different solutions to this challenge through techniques like re-enactment as well as visual methods such as photography and film, many of these being used in museum contexts. In this article we focus on film, as we believe it has more to offer for knowledge production than its current use in studies of history predominantly as an engagement tool in research communication, as a final research ‘output’ or ‘illustration’ for texts and objects. We suggest that film can be an important research method to: a) trace the research process; b) enhance collaboration especially in group projects; c) analytically help researchers to amplify sensorial details, through the possibility to rewind, freeze and focus on embodied action; and d) as a means of sharing research instead of text. Thus, extending from Lucien Taylor’s suggestion that ethnography could be conducted ‘filmically’, we argue that, like anthropologists, historians and museum specialists might also accommodate film as part of a serious research methodology, especially when it comes to respecting the integrity of embodied contributions to the history of science and medicine.